An integrative water quality index and multivariate modeling approach to assess surface water quality, trophic status and nutrient source apportionment in a large tropical reservoir, Hirakud–the longest earthen dam in Asia - Pranab Gogoi; Basanta Kumar Das; Satish Kumar Koushlesh; Canciyal Johnson; Ramesh Malick; Ajoy Saha; Taniya Kayal; Ratul Chakraborty; Laxmidhar Pradhan; Archan Kanti Das (Applied Water Science)
Abstract The present study aimed to evaluate the spatio-temporal variations of surface water quality and trophic status of Hirakud reservoir, India based on the study of two annual periods (2022–2024). Nineteen limnological parameters were assessed seasonally at 14 sampling sites throughout the reservoir. Water variables showed significant (p < 0.05) spatial and seasonal variations where seasons had more impact on physicochemical variables. The calculated Arithmetic Weighted WQI value determined the reservoir water to be of ‘good’ water quality, especially in the pre- and post-monsoon period. However, during monsoon, increased turbidity was found to be a single potent factor for drastic deviation in WQI, rated as ‘poor to very poor’ water quality. Overall, the entire reservoir was in a mesotrophic state, with Carlson’s Trophic State Index (CTSI) ranging between 40.44 and 50.95. The insignificant (p > 0.05) spatio-temporal variation of CTSI value, which indicates the biological productivity of the reservoir, maintains its homogeneity. The land use land cover map was created for the reservoir with an overall accuracy Kappa index value of 0.85. The present study also evaluated the evolution of eutrophication in relation to Chl a using the Generalized Linear Model (GLM) and BEST Biota––Environmental Matching (BIO–ENV). Our models suggest that water variables (dissolved oxygen, PO4 3−, transparency, and electrical conductivity) were the best explained variables for deviating Chl a in reservoir water. Furthermore, the BIO–ENV model suggests that other factors (geographic and climatic) are equally responsible for the local evolution of eutrophication in the reservoir, including allochthonous inputs mainly by feeder river.